Identifying drought tolerant germplasm through multiplexing polygenic traits in soybean (Glycine max L. Merrill): Identifying drought tolerant germplasm through multiplexing polygenic traits in soybean (Glycine max L. Merrill) - G K SATPUTE; M ARYA; S GUPTA; V S BHATIA; D RAMGOPAL; M B RATNAPARKHE; S CHANDRA; MAHARAJ SINGH; S NAGAR; V G KAMBLEY; SANJAY PANDEY; G KUMAWAT; et al. (Journal of Oilseeds Research, 2020)
Soybean being an important seed legume, majority of its cultivated area reported the highest frequency of drought occurring during seed fill growth stage. Identifying novel germplasm for drought tolerance, following multi- tier selection scheme, is an activity in plant genetic resources (PGR) fetching importance in developing climate smart drought tolerant soybean varieties. Multiplexing polygenic drought tolerance related traits into a multi-trait index is an efficient system which identified 3 (TGX-709-50E, J-732 and EC-107407) drought tolerant soybean germplasm. Molecular analysis of these germplasm is in progress for identifying putative drought tolerant genes.